Convergence as a fundamental principle of science and philosophy of education in the XXI century - O. E. Baksansky (Сеченовский вестник, 2014)
This article deals with the current theoretical and practical aspects of science and philosophy of education. The development of multi-level integrative processes suggests a new type of integration in the system of modern science. The newest areas of science development associated with the nano-, bio-, info-, cognitive (NBICS) science and technology give an example of convergent processes.